Pengaruh Kualitas Pelayanan Dan Kepercayaan Terhadap Kepuasan Nasabah Pada Lembaga Perkreditan Desa (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
The aim of this research is to determine the influence of service quality and trust on customer satisfaction both directly and indirectly, so it is important for LPD Tegal Darmasaba to provide optimal service and be able to provide solutions to customer complaints, so that customers will feel satisfied with what is provided by LPD Tegal Darmasaba. In this research, the data sources used are primary data and secondary data. The population in this research was 4,366 customers. The sample used in this research was 82 respondents, using the Slovin formula. The technique used in this research is multiple linear regression analysis. From the research results, it was found that: Service quality has a significant positive effect on customer satisfaction. Trust has a significant positive effect on customer satisfaction. Service quality and trust have a significant positive influence on customer satisfaction at LPD Tegal Darmasaba. The advice that can be given to the leaders and employees of LPD Tegal Darmasaba is that they can improve the quality of service to customers and employees must be friendlier in serving customers, serving customers quickly and efficiently. This can later increase customer satisfaction and also increase customer trust.